KEY PROBLEMS OF MODERN SPAIN - A. . Orlov (Ибероамериканские тетради, 2016)
Adoption in 1978 of the new Constitution became a watershed between two Spains - old, dictatorial and modern, socially oriented, democratic. As a result of shown by leaders of the main political parties, labor unions and pragmatic part of the armed forces responsibility for the future of the country, the compromise solutions of a number of burning issues have been found that created necessary conditions for stable development of Spain for three next decades. Nevertheless over the years there were new problem knots which were distinctly shown during the financial and economic crisis 2008 which painfully struck across Spain, and the long-term depression which followed it. After the national elections to General Courts which took place on December 20, 2015 it became obvious that actually two-party system existing throughout the most part of the post-Franco period in Spain consigned to the past. It was succeeded by four-party system that excessively complicates process of formation of the stable government. In the practical plane there is a question of need to make changes into the existing Constitution of Spain (country federalization, fixing in the Fundamental law of the new civil and political rights and freedoms, revision of bases of an electoral system, reform of the Senate, etc.). The Catalan nationalism / separatism and corruption in the top echelons of power are distinguished from the burning issues of modern Spain. In article the conclusion is drawn that Spain faces a responsible choice today, on what way to go: or to continue the inertial movement on the route offered by the Spanish conservatives or to decide on changes, to initiate something similar to «the second transit» for what can call the left forces.